An R package for simulating metapopulation dynamics and range expansion under environmental change. (July 2016) - Mestre, Frederico; Cánovas, Fernando; Pita, Ricardo; Mira, António; Beja, Pedro
Abstract: The metapopulation paradigm is central in ecology and conservation biology to understand the dynamics of spatially-structured populations in fragmented landscapes. Metapopulations are often studied using simulation modelling, and there is an increasing demand of user-friendly software tools to simulate metapopulation responses to environmental change. Here we describe the MetaLandSim R package, which integrates ideas from metapopulation and graph theories to simulate the dynamics of real and virtual metapopulations. The package offers tools to (i) estimate metapopulation parameters from empirical data, (ii) to predict variation in patch occupancy over time in static and dynamic landscapes, either real or virtual, and (iii) to quantify the patterns and speed of metapopulation expansion into empty landscapes. MetaLandSim thus provides detailed information on metapopulation processes, which can be easily combined with land use and climate change scenarios to predict metapopulation dynamics and range expansion for a variety of taxa and ecological systems. Highlights: We present the new freely available R package MetaLandSim. MetaLandSim balances modest data requirements with usability and output quality. MetaLandSim simulates metapopulation dynamics in dynamic landscapes. MetaLandSim simulates metapopulation range expansion into empty landscapes. MetaLandSim estimates dispersal kernels to refine forecasts of species range shifts.